Establishment of Natural Hazards Mapping Criteria Using Analytic Hierarchy Process (AHP) - Morales, Florentino F.; de Vries, Walter Timo (Frontiers in Sustainability, 2021)
Despite the large number of studies on natural hazards mapping and modeling, an increasing number of disasters still occur worldwide. Floods, landslides and tsunamis among others consistently hit vulnerable countries, resulting in increasing death tolls and economic losses in the last decades. The increased reliability of available hazard maps are still insufficient when not fully integrated and incorporated in the land use plans of respective communities. As a pro-active and preventive approach in combatting disasters, land use planning requires active participation of the relevant stakeholders. This study derives the most crucial criteria in the eyes of planners, experts and decision makers for natural hazards mapping as part of land use planning and part of disaster risk reduction. These stakeholders and experts establish criteria for flood, landslide, earthquake and storm surge hazard mapping through Multi-criteria Evaluation (MCE). The MCE technique compares the relative merits of different spatially related criteria following the Analytic Hierarchy Process (AHP) through pair-wise comparisons of criteria by experts and the decision makers. This research process derives a general and consistent list of criteria for hazard mapping which can be used in subsequent GIS analysis. Results further show the advantages of using AHP in a multi-criteria analysis for decision-making and compliance.